2003
DOI: 10.1364/josab.20.001486
|View full text |Cite
|
Sign up to set email alerts
|

Optical-limiting response of rare-earth metallo-phthalocyanine-doped copolymer matrix

Abstract: The nanosecond optical-limiting characteristics (at 532 nm) of some rare-earth metallo-phthalocyanines (Sm(Pc)2, EU(PC)2' and LaPe) doped in a copolymer matrix of poiy(methyl methacrylate) and methyl-2cyanoacrylate have been studied for the first time to our knowledge. The optical-limiting response is attributed to reverse saturable absorption due to excited-state absorption. The performance of LaPc in a copolymer host is studied at different linear transmissions. The laser damage thresholds of all the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…7. As previously reported, the linear nature of the graph is a clear indication that RSA is the main mechanism causing optical limiting in the studied samples [50,51]. As earlier stated, the RSA in these complexes is due to the excited-state absorption (with contributions from both the singlet and triplet state.…”
Section: Nonlinear Absorption (Nla) Behaviorsupporting
confidence: 70%
“…7. As previously reported, the linear nature of the graph is a clear indication that RSA is the main mechanism causing optical limiting in the studied samples [50,51]. As earlier stated, the RSA in these complexes is due to the excited-state absorption (with contributions from both the singlet and triplet state.…”
Section: Nonlinear Absorption (Nla) Behaviorsupporting
confidence: 70%
“…It is therefore important to verify the existence of RSA at 532 nm, particularly because LnPc 2 complexes have a BV band around this region which is likely to contribute to ground state absorption. To investigate the RSA existence, we follow the previous reported procedure [55], by plotting natural logarithm of I in /I out ratio against the I in À I out difference. If RSA is strongly affected by the other competing processes, the fitting is expected to deviate quite strongly from the linearity.…”
Section: Optical Limiting Propertiesmentioning
confidence: 99%
“…This gives rise to the phenomenon of Reverse Saturable Absorption (RSA) as a consequence of multiphoton absorption [11,12]. Nitschke et al reported the first study of the NLO properties of Pc nanoparticles fabricated from tBu 4 PcZn, (PhS) 4 PcZn, tBu 4 PcCu and (PhS) 4 PcH 2 [13,14]. The actual particle size, when was on the nanometer scale, was found to be molecule-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The significant improvement in the NLO response of the nanoparticles over solutions of the same phthalocyanines was obtainable. As an example, for the molecular and nanoparticle (PhS) 4 PcZn sample, the solution of this sample exhibited the nonlinear absorption coefficient (b I ) z (4.0 AE 0.8) Â 10 À10 cm W À1 while its associated nanoparticle exhibited a b I value approximately 5.3 times larger at…”
Section: Introductionmentioning
confidence: 99%